2020
DOI: 10.1200/go.20.00350
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Sciences Education in Africa: An Assessment of Current Training Practices and Evaluation of a High-Yield Course in Radiation Biology and Radiation Physics

Abstract: PURPOSE Formal education in the radiation sciences is critical for the safe and effective delivery of radiotherapy. Practices and patterns of radiation sciences education and trainee performance in the radiation sciences are poorly described. This study assesses the current state of radiation sciences education in Africa and evaluates a high-yield, on-site educational program in radiation biology and radiation physics for oncology and radiation therapy trainees in Africa. METHODS An anonymous survey was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The significant increase in mean Likert scale results confirm the hypothesis first established during our pilot program. Previous studies in developing countries also support these outcomes ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 63%
“…The significant increase in mean Likert scale results confirm the hypothesis first established during our pilot program. Previous studies in developing countries also support these outcomes ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 63%
“…The need for an accelerated building of capacity to match the demand is evident, not only for basic knowledge but also for transitioning to more modern techniques and much can be achieved by international collaboration 24 25. Formal education in the radiation sciences improves the safety of radiotherapy delivery and this can be achieved by innovative ways such as blended e-learning and short intensive on-site courses 25. An example of a successful transitioning training program is the Access to Care initiative that trained 13 teams from eight African countries over a period of 5 years.…”
Section: Availability and Maintenance Of Equipmentmentioning
confidence: 99%
“…24 25 Formal education in the radiation sciences improves the safety of radiotherapy delivery and this can be achieved by innovative ways such as blended e-learning and short intensive on-site courses. 25 An example of a successful transitioning training program is the Access to Care initiative that trained 13 teams from eight African countries over a period of 5 Review years. This initiative was a collaboration between industry and academic institutions that aimed to train professionals intensively on how to implement and maintain three-dimensional techniques in radiotherapy delivery.…”
Section: Radiotherapy Workforcementioning
confidence: 99%
“…21 The CDH-MDA academic partnership was first established in 2015 and has included in-country clinical education workshops and telementoring 17 and an annual radiation biology and physics course. 18 In addition, core faculty members from CDH and MDA meet weekly via teleconference to discuss joint initiatives and research. We found that the longstanding partnership between CDH and MDA and consistent communication were instrumental in the success of the present program by allowing for shared planning and program development, allocation of resources (ie, protected time for registrars), and rapid response to issues as they arose.…”
Section: The Virtual Cdh-mda Clinical Research Training Program Formentioning
confidence: 99%
“…The MD Anderson Cancer Center (MDA) in Houston, TX, and the Cancer Diseases Hospital (CDH) in Lusaka, Zambia, have an established academic partnership that includes telehealth mentoring through Project ECHO 17 and an annual high-yield course in radiation biology and physics. 18 The CDH Specialized Training Program in Clinical and Radiation Oncology enrolled its first fellows in 2018 and will graduate the country's first cohort of locally trained oncologists in 2022. A significant area of need was jointly identified as a structured clinical research training program.…”
Section: Introductionmentioning
confidence: 99%